Cyclosporin A inhibits rat mast cell activation - Dráberová, L (European journal of immunology, 1990)
To gain further insight into the mechanism of immunosuppression by cyclosporin A (CyA), the effect of CyA on activation of isolated rat mast cells was studied. CyA alone, up to a concentration of 80 microM, had no effect on histamine release from unstimulated mast cells in both calcium-supplemented and calcium-free media. However, in the presence of extracellular calcium CyA inhibited, in a dose-dependent manner (range from 8 nM to 80 microM), histamine release induced by three unrelated secretagogues, the compound 48/80, calcium ionophore A23187 and concanavalin A plus phosphatidylserine. In the absence of extracellular calcium no, or only a marginal, effect of CyA on histamine release induced by the secretagogues was observed. CyA also inhibited the uptake of radiolabeled calcium by the secretagogues-treated cells. However, CyA did not interfere with the activation-related early increase in the intracellular free calcium. Thus, CyA-mediated inhibition of mast cell activation is related to external calcium uptake. These results indicate that rat mast cells belong to the immune cell types whose activity can be modulated by physiologically relevant concentrations of CyA.
Keywords: inbrední kmeny potkanů; Calcium; vápník; Rats, Inbred Strains; Histamine Release; Mast Cells; Rats; In Vitro Techniques; zvířata; mastocyty; techniky in vitro; Cyclosporins; uvolňování histaminu; konkanavalin A; krysa rodu Rattus; Concanavalin A; cyklosporiny; Animals